Abnormal mismatch repair and other clinicopathologic predictors of poor response to progestin treatment in young women with endometrial complex atypical hyperplasia and well‐differentiated endometrial adenocarcinoma: a consecutive case series. (27th January 2017) - Zakhour, M; Cohen, JG; Gibson, A; Walts, AE; Karimian, B; Baltayan, A; Aoyama, C; Garcia, L; Dhaliwal, SK; Elashoff, D; Amneus, M; Walsh, C
Abstract : Objective: To report the response to progestin therapy in young women with endometrial complex atypical hyperplasia (CAH) or FIGO grade 1 endometrial adenocarcinoma (FIGO 1 EAC) based on clinicopathologic features, including abnormal DNA mismatch repair (MMR) by immunohistochemistry (IHC). Design: Consecutive case series. Setting: Olive View‐UCLA Medical Center in Sylmar, CA, USA, and Cedars‐Sinai Medical Center in Los Angeles, CA, USA. Population: Women ≤55 years old with CAH or FIGO 1 EAC. Methods: Response to progestin therapy in 84 consecutive patients was assessed based on clinicopathologic factors, including age, body mass index (BMI), initial histology, and IHC staining for MMR proteins. Main outcome measures: Rates of abnormal MMR protein expression and response to progestin therapy were determined. Results: Six (7%) patients had abnormal IHC staining, of whom five (83%) had FIGO 1 EAC at initial diagnosis. Following progestin treatment, none of the endometrial lesions in patients with abnormal IHC for MMR proteins had resolution of hyperplasia or malignancy, in contrast to 41 (53%) with normal staining ( P = 0.028). Age ≤40 years and initial lesion (CAH versus FIGO 1 EAC) were predictors of response to progestin; BMI was not. Conclusions: In this cohort, 7% of women ≤55 years of age with CAH or FIGO 1 EAC had loss of MMR proteins by IHC. These patients had a higher incidence of invasive cancer and a lower incidence of resolution with progestin therapy. Tweetable abstract: Abnormal MMR protein expression predicts poor response to progestins in young women with CAH or FIGO 1 EAC. Tweetable abstract: Abnormal MMR protein expression predicts poor response to progestins in young women with CAH or FIGO 1 EAC.